Flood Indicator System (FIS) - Ikhsan, Muhammad Faiz; Jamil, Muhammad Faiz Irsyad; Mohd Irwan, Wan Muhammad Izzat Fitri; Idris, Nur'ain (Multidisciplinary Applied Research and Innovation, 2024)
Flood indicator system (FIS) is a water sensor that can detect the rise of water to alert the community about the possibility of flood disaster. The main focus of this project is to develop a simple system that can read water level increases but with alert function to send the information of water that increase to hazard level to the surrounding community. The existing system can analyze the increase of water to determine the possibility of flood to occur but this system is not so efficient when facing the sudden flood where the water level rise quickly and effect information transfer to the community about the disaster that can lead to serious damage and loses. In order to ensure the information transfer, this project will equip with message alert system that can send an alert message to the community as an early-stage alert that can help them to evacuate before the disaster could occur. This information transfer method is effective as it can ensure the community will get the message straight from their phone. A program using microbit makecode had been used to make this system able to detect the increases of water and create the message required to alert the surrounding community about the hazard level of water. In this project, the functions of the flood indicator system program to help the evacuation of community when facing the flood that can avoid major losses and loss of lives. The outcome of this study, FIS is programed to help detect the increase of water and possibility of flood using the water sensor and send an alert message as early precaution to help evacuation. Therefore, it will be more efficient to use FIS to help the community facing the flood disaster.